2011
DOI: 10.1093/ajae/aar012
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐ and Long‐Term Participation in Microcredit: An Evaluation Using a New Panel Dataset from Bangladesh

Abstract: The objective of this paper is to estimate the impacts of medium-and long-term participation in microcredit programs. It utilises a new and large panel dataset collected from treatment and control households from 1997 to 2005. The data enables us to identify continuing participants in the program as well as newcomers and leavers. We employ di¤erent estimation strategies including triple-di¤erence and propensity score matching methods to control for selection bias. The impact estimates indicate that the bene…ts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 27 publications
2
52
0
Order By: Relevance
“…But in the past two decades around the world, it is found that mostly the least developing countries have seen the development of new microfinance technologies (Islam, 2011;Berhane & Gardebroek, 2011) that have successfully lowered the risk and the cost of lending to poor entrepreneurs and households. Microcredit obviously reduces the financial vulnerability among the poor by building assets, giving proper education, providing emergency assistance during natural disasters, generating income and contributing to female empowerment (Khandker, 2005;Shahriar, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…But in the past two decades around the world, it is found that mostly the least developing countries have seen the development of new microfinance technologies (Islam, 2011;Berhane & Gardebroek, 2011) that have successfully lowered the risk and the cost of lending to poor entrepreneurs and households. Microcredit obviously reduces the financial vulnerability among the poor by building assets, giving proper education, providing emergency assistance during natural disasters, generating income and contributing to female empowerment (Khandker, 2005;Shahriar, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Competition among increasing numbers of MFIs has been diffused extensively in product development, service offered, customer relationship and management efficiency (Khavul, 2010). The level of proficiency in managing the microfinance institutions can be gauged by the fact that while most MFIs recognize the importance of client retention, however only a few have designed business strategies to maximize customer loyalty (Churchill, 2000;Islam, 2011). Retaining clients is very important for the MFI's very survival because it not only can reduce the MF's administrative costs, but it can also lower default risks and increase the average loan balance as well as the institutional financial productivity (Pagura et al, 2001;Mustafa, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations